Zinc serum levels and common mental disorders: An integrative review (Research, Society and Development, 2021)
The objective was to analyze the scientific production about the current evidence on the relationship between serum zinc concentrations and common mental disorders. This is an integrative literature review, carried out between March and July 2020, using the PICOS strategy for the selection of articles. The databases were accessed through the Capes Virtual Health Library and Capes Journals Portal, corresponding to: Science Direct, Springer Science, Medline / Pubmed, ProQuest LLC, AGRIS, Bentham Science Publishers, Cengage Learning, Web of Science, John Wiley & Sons, Scopus, Directory of Open Access Journals, Maney Publishing, and SAGE Publications. Seven publications were analyzed that evaluated individuals of both sexes, in different age groups, based on observational analytical studies. The studies listed for analysis, conducted in groups of different age groups and sample numbers, showed similar results, demonstrating the prevalence of reduced concentrations of zinc in the blood of patients with depression and / or anxiety. The correlation between serum zinc concentrations and common mental disorders, in most results, converges to evidence that serum zinc deficiency is significantly associated with depressive and anxiety symptoms. Based on the designs of the investigations listed, they cannot determine a causal relationship between zinc and depressive and anxiety symptoms. However, it is plausible to state, based on the results and physiological mechanisms of zinc, that the low peripheral concentration of this element may play a role in the pathophysiology of some domain of mental function.